2015
DOI: 10.1105/tpc.114.132209
|View full text |Cite
|
Sign up to set email alerts
|

In Planta Variation of Volatile Biosynthesis: An Alternative Biosynthetic Route to the Formation of the Pathogen-Induced Volatile Homoterpene DMNT via Triterpene Degradation in Arabidopsis Roots

Abstract: Plant-derived volatile compounds such as terpenes exhibit substantial structural variation and serve multiple ecological functions. Despite their structural diversity, volatile terpenes are generally produced from a small number of core 5-to 20-carbon intermediates. Here, we present unexpected plasticity in volatile terpene biosynthesis by showing that irregular homo/ norterpenes can arise from different biosynthetic routes in a tissue specific manner. While Arabidopsis thaliana and other angiosperms are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 77 publications
4
113
1
1
Order By: Relevance
“…The biosynthetic pathway of DMNT presented here is consistent with previous feeding experiments utilizing deuterated nerolidol, which was converted to DMNT in nine dicotyledonous plant species (Donath and Boland, 1995). A very different pathway of DMNT biosynthesis was described for Arabidopsis roots, in which this compound is formed by degradation of the triterpene arabidiol (Sohrabi et al, 2015). In maize roots, the formation of DMNT by this or any other pathway was not observed .…”
Section: Discussion Association Mapping Identified the Pathways Of Hosupporting
confidence: 75%
See 3 more Smart Citations
“…The biosynthetic pathway of DMNT presented here is consistent with previous feeding experiments utilizing deuterated nerolidol, which was converted to DMNT in nine dicotyledonous plant species (Donath and Boland, 1995). A very different pathway of DMNT biosynthesis was described for Arabidopsis roots, in which this compound is formed by degradation of the triterpene arabidiol (Sohrabi et al, 2015). In maize roots, the formation of DMNT by this or any other pathway was not observed .…”
Section: Discussion Association Mapping Identified the Pathways Of Hosupporting
confidence: 75%
“…degradation (Sohrabi et al, 2015). The P450 enzyme involved in this alternate pathway, CYP705A1, has no apparent sequence similarity to maize CYP92C5 and CYP92C6 (Figure 14).…”
Section: Two P450 Enzymes Are Responsible For the Emission Of Dmnt Anmentioning
confidence: 99%
See 2 more Smart Citations
“…All these stressors induce volatile induction via the same general pathways, though there is a degree of attacker specificity in the phytohormonal 'signal signature' (De Vos et al, 2005;Tumlinson & Engelberth, 2008). Phytopathogens can also induce the emission of volatile compounds which are typically and traditionally associated with herbivory, such as GLVs, (E,E)-4,8,12-trimethyltrideca-1,3,7,11-tetraene ((E,E)-TMTT) (Shiojiri et al, 2006;Attaran et al, 2008;Scala et al, 2013) or (E)-DMNT (Sohrabi et al, 2015), all of which show that these volatile compounds can also have important roles in direct plant defense against pathogens. We showed that B. nigra plants emit high levels of GLVs (Fig 4b), particularly (Z)-3-hexen-1-ol, when challenged with the virulent pathovar.…”
Section: Discussionmentioning
confidence: 99%